Climate variability, water supply, sanitation and diarrhea among children under five in Sub-Saharan Africa: a multilevel analysis. (6th April 2022) - Kemajou, Donald Njatang
Abstract: Climate variability is expected to increase the risk of diarrhea diseases, a leading cause of child mortality and morbidity in Sub-Saharan Africa (SSA). The risk of diarrhea is more acute when populations have poor access to improved water and sanitation. This study seeks to determine individual and joint effects of climate variation, water supply and sanitation on the occurrence of diarrhea among children under five in SSA using multilevel mixed-effect Poisson regression including cross-level interaction. We merged 57 Demographic and Health Surveys (DHS) from 25 SSA countries covering the period 2000–2019 with climatic data from the DHS geolocation databases. The results of the research indicate that 77.7% of the variation in the occurrence of diarrhea in Sub-Saharan households is due to climatic differences between clusters. Also, a household residing in a cluster with a high incidence of diarrhea is 1.567 times more likely to have diarrhea cases than a household from a cluster with a low incidence. In addition, when average temperature and rainfall increase, households using unimproved sanitation or unimproved water have more cases of diarrhea. For SSA, the results of the multilevel analysis suggest the adoption at both levels; macro (national) and micro (household), of climate change adaption measures in the water sector to reduce the prevalence of diarrhea. HIGHLIGHTS: Diarrhea remains the second driving causes of under-five years old children's mortality in developing countries. 77% of the variation in the occurrence of diarrhea is due to climatic differences in SSA countries. Increases in average rainfall and average temperatures lead to an increase in the occurrence of diarrhea in households using unimproved sanitation facilities or unimproved water.